Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.22271/plants.2021.v9.i3a.1275
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacognostical, biochemical activities and zootechnical applications of Psidium guajava (Myrtaceae), plant with high medicinal value in tropical and subtropical parts of the World: A review

Abstract: In the search for new molecules capable of treating intestinal parasitosis with less risk in the short, medium and long term, the potential of medicinal plants is explored. Psidium guajava is plant used traditional medicine to treat gastrointestinal disorders and intestinal parasitosis. According to the synthesis of reviews presented here, very few studies have been devoted to the evaluation of anthelmintic activities of Psidium guajava. Psidium guajava has secondary metabolisms responsible for its demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
1
3
0
1
Order By: Relevance
“…In addition, similar results have been found in other works, in which it was reported that flavonoids from Thymus vulgaris are used as an antibiotic against different pathologies [40,41]. Thymus vulgaris has several medical uses, including the treatment of intestinal infections [42] and gastric inflammation [43,44]. Importantly, the analysis of the essential oils of thymus vulgaris through the use of GC showed the richness of its oils in thymol and carvacrol, which are involved in the antimicrobial effect of this plant [45].…”
Section: • Thymus Vulgarissupporting
confidence: 87%
“…In addition, similar results have been found in other works, in which it was reported that flavonoids from Thymus vulgaris are used as an antibiotic against different pathologies [40,41]. Thymus vulgaris has several medical uses, including the treatment of intestinal infections [42] and gastric inflammation [43,44]. Importantly, the analysis of the essential oils of thymus vulgaris through the use of GC showed the richness of its oils in thymol and carvacrol, which are involved in the antimicrobial effect of this plant [45].…”
Section: • Thymus Vulgarissupporting
confidence: 87%
“…40.14 39.67 -40.74 VII C at (6) , Cat (2) , Cat (2) , Gui (1) , Myr (2) , Psi (1) 43.80 The GC% values of the evaluated 137 individuals ranged from 34.33% for an individual of P. guineense to 48.95% for an individual of P. myrtoides. The largest intraspecific variations (~ 10%) were in P. myrtoides and P. cattleyanum, which are species that also show nuclear 2C value intraspecific variation.…”
Section: Groupmentioning
confidence: 98%
“…Accesses Mean value Minimum and maximum value 2C value I Gua (6) , Gua (17) , Gua (31) , Mac (1) , Obl (1) 0.96 0.90 -1.10 II Aci (4) , Cat (1) , Hib (14) , Gui (7) , Psi (7) 1.94 1.80 -2.08 III Cat (19) , Cat (11) , Cat (5) , Cat (30) , Cat (30) , Myr (6) , Myr (18) , Myr (30) , Ruf (1) , Psi (1) 3.51 2.72 -4.38 IV Cat (5) , Gau (1) , Gau (28) ,Fri (1) , Psi (3) 4.88 4.47 -5.19…”
Section: Groupmentioning
confidence: 99%
See 2 more Smart Citations